The Relation Between Multi Actors and Local Reform in Solo City During Joko Widodo’s Leadership Era (2005-2012) - Bulan, Wahidah R. (Research and Development Agency Ministry of Home Affairs, 2016)
This study explored power relation of Jokowi as mayor of Solo City and his efforts to create inclusive populist policies in the case of street vendors’ arrangement and resettlement of people on the banks of Solo River. Specifically, this study explores how Jokowi build his relations with many actors, namely, how the relations can be established, who were they, how were the relationships between Jokowi and CSO (Civil Society Organization) and CSA (Civil Society Activist) as the agencies with serious interest in pursuing reform, and how these relations contribute to achieving local reform agenda. By using qualitative approach with case study strategy as the methodology, this study was conducted from December 2010 to early 2012 and obtained some results as follows: there are some strong enough relations between Jokowi with state and non-state actors, which exist as the attempt to overcome the structural constraints (limited human resources) and because of the similar agendas between Jokowi and those actors (especially with CSO and CSA), and that the relations (with CSO and CSA) are proven effective in helping to achieve local reform agenda progressively. The study also refines Tilly’s theory (1978) on several aspects, namely: the variant of member and challenger, the radical challenger, and neutral, and that the positions of challenger or member are not permanent (depend on the issues).